Pengembangan Model Konservasi Discharge Planning Terstruktur Terhadap Individual And Family Self Management Diabetic Foot Ulcer - Yohanes Andy Rias; Elsye Maria Rosa; Falasifah Ani Yuniarti (Universitas Muhammadiyah Yogyakarta, 2016)
Background : Diabetic foot ulcers generally causing low selfmanagementbehaviorsandqualityoflife, requiring of nursing intervention to improve individual and family selfmanagement. The intervention is the process of behavioral changes in patients and families through health education. Health education for participants and families can be implemented through discharge planning to provide the information, to identify needs and to plan the return and to prepare participants to leave the health service, beginning at admission until discharge, including diabetic foot ulcers client.Objective: To develop a model of the structured discharge planning conservation for individual and family self-management of diabetic foot ulcers.Research Methodology: This study using action research design by collecting data through The Conceptual Content Cognitive Map (3CM) and Triangulation followed by presenting descriptive data. The number of participants in this study are 4 patient and 4 family for pre action research with accidental sampling, 6 nursing for action research with purposive sampling, 4 experts for triangulation with accidental sampling, and 10 nursing and practitioners with accidental sampling for validation of structured discharge planning conservation tools for individual and family self- management of diabetic foot ulcers.Results: There are categories of participants needs in the individual and family selfmanagement, which are:(a) knowledge, (b) beliefs, (c) self-regulation, (d) social facilities, (e) self management behaviors. The results of action research is the completion of discharge planning conservation tools that structured by four cycles of study.Conclusion: The presence of structured discharge planning conservation tools expected to increase individual and family self management. Necessary to implementation and validatin of tools model structured discharge planning conservationKeywords: Diabetic foot ulcers, Tools, Structured discharge planning conservation, Individual and family self management.